Local Heat Transfer to an Evaporating Sessile Droplet in an Electric Field - Robinson, Anthony; Gibbons, Michael (My University, 2016)
Local heat transfer of an evaporating sessile droplet under a static electric field is an underdeveloped topic. In this research an 80 μl water droplet is placed in the centre of a 25 μm thick stainless steel substrate. A static electric field is applied by an electrode positioned 10 mm above the substrate. A high speed thermal imaging camera is placed below the substrate to capture the thermal footprint of the evaporating droplet. Four electric fields were characterised; 0, 5, 10 and 11 kV/cm. As the electric field is increased the contact angle was observed to decrease. The local heat flux profile, peak and radial location of this peek were observed to be independent of the applied electric field for all test points for this working fluid and surface combination.
PUBLISHED
Keywords: Electric fields; Heat transfer